Keyhole anterolateral thigh flap: A special way of partition for reconstruction around a protruding structure or cavity/tunnel - SAÇAK, BÜLENT (My University, 2015)
Background: Anterolateral thigh (ALT) flap is now a workhorse flap for reconstruction of skin and soft tissue defects. However, there are some drawbacks in its application, and revisions are often needed after surgery. Here, we present the results of the use of a special type of partition for ALT flap based on the concept of perforator flap vascular anatomy for reconstruction around a protruding structure, a cavity or a canal, in patients. Patients and methods: We used the keyhole design for reconstruction with ALT flaps in five patients. Wounds involved circumferential soft tissue defects around the following structures: thumb (two cases), penis, ear canal, and anus. Defects arose following excision of scar contracture, arterio-venous malformation, Paget\"s disease, squamous cell carcinoma, and Fournier\"s gangrene, respectively. The ALT flap was raised based on perforators. The flap was partitioned with a keyhole incision performed in a zone between two perforators or distal to them, avoiding complete split of the flap and minimizing disruption of its vascular crossover. The circulation of the flap was well preserved. The closure of the flap had no tension. Results: All the flaps had 100% viability without partial loss. Mean follow-up was of 7.4 months (range 4-11 months). Significant functional improvement was achieved in the two thumb cases. Adequate patency of the ear and anal canals was obtained. No contracture around the penis was observed. Conclusion: The keyhole design may be a valuable method of partition of the ALT flap for specific reconstructions around protruding organs, cavities, or canals. (c) 2015 Wiley Periodicals, Inc. Microsurgery 35:356-363, 2015.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery